Prevalence and Predictors of Metabolic Syndrome among Rural Women in West Bengal, India - Biswas, Sunanda; Das, Arabinda; Biswas, Souti (International Journal of Psychosocial Rehabilitation, 2020)
Metabolic syndrome (MS) is a combination of risk factors for the cardiovascular and type 2 diabetes. Our objective here is to identify the prevalence of MS among rural adult women in West Bengal, India and the known determinants identified therein. A cross-sectional community-based study was conducted in four West Bengal villagers in Nadia district where 161 women (20 yrs) recruited systematic multi-stage sampling of random samples. Demographic data were collected via a questionnaire which was pre-tested. We measured blood pressure and anthropometric scales. Biochemical studies were performed on the blood samples collected after overnight fasting. Part III (NCEP / ATP-III) National Cholesterol policy framework / Adult Treatment Recommendations for Indians and the International Diabetes Federation (IDF) proposed revised waist circumference metabolic syndrome criteria. The prevalence of metabolic syndrome was 27.33 per cent among women over the age of 20. Substantially elevated levels (P-value < 0.01) have been observed in cardio-vascular disease parameters viz. Cholesterol (total, mg / dl), HDL cholesterol , triglycerides, blood pressure (systolic and diastolic) among women with MS. Females with MS were significantly correlated with body mass index ( BMI), waist circumference ( WC), fasting blood sugar and blood pressure (P-value < 0.01) which have been independent predictors of MS. However, studies with a larger sam should be conducted to confirm these findings.